Train Type Identification at S&C - Martina Kratochvílová; Jan Podroužek; Jiří Apeltauer; Ivan Vukušič; Otto Plášek (Journal of Advanced Transportation)
The presented paper concerns the development of condition monitoring system for railroad switches and crossings that utilizes vibration data. Successful utilization of such system requires a robust and efficient train type identification. Given the complex and unique dynamical response of any vehicle track interaction, the machine learning was chosen as a suitable tool. For design and validation of the system, real on-site acceleration data were used. The resulting theoretical and practical challenges are discussed.